Scope Management in Industry 4.0 Projects - Nurdiansyah Nurdiansyah; Masdar Masud; Serlin Serang (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
This study investigates the implementation of marketing innovations within the framework of Industry 4.0, focusing on Asian corporate culture. Companies must innovate in the rapid globalization and digital transformation era to stay competitive and meet evolving client demands. The research identifies 15 critical attributes essential for marketing innovation in Industry 4.0, including augmented reality, virtual cryptocurrencies, and the Internet of Things (IoT). These innovations represent a blend of technological and non-technological advancements companies use to enhance their marketing strategies. The study examines the impacts of these innovations through a survey of 50 companies utilizing Industry 4.0 technologies. Key findings indicate significant impacts such as increased competitiveness, improved customer communication, and enhanced work efficiency. Larger companies and those in the automotive sector rate these impacts more highly, reflecting their greater reliance on technological advancements. Additionally, the study reveals that cultural factors influence the perception of these impacts, with companies in Asian cultures exhibiting varied responses compared to those with a global business culture. The pilot study utilized qualitative and quantitative methods, including structured surveys and descriptive statistical analysis. The results underscore the importance of effective scope management in successfully implementing Industry 4.0 projects, emphasizing the need for clear goal-setting, resource allocation, and change control. The research highlights the necessity for organizations to adapt their corporate culture and develop innovative marketing strategies tailored to their specific contexts. These insights offer practical recommendations for optimizing project outcomes and maintaining competitiveness in the digital age.